System Analysis Of Inventory Information On Raw Material Companies - Hidayat, Wahyu; Pramono, Bayu; Afdulloh, Mohhammad (APTISI Transactions on Management (ATM), 2019)
In the era of increasingly rapid development of information technology, the use of computers in every Indonesian company is very important to support information needs. This is definitely mandatory, because with a computerized system all processes ranging from data processing to other important documents can be arranged neatly so that it can facilitate data storage and search. Problems faced in the inventory information system at the company are usually lacking an accurate, fast, and precise information system so that it is less optimal and produces all accurate and relatively long reports. The purpose of the research conducted by the author is to analyze the information system that runs on the raw material company. The methodology used is the system development life cycle approach starting from analyzing the system that runs through UML (Unified Modeling Language) to describe the running system analysis and analysis of the proposed system so as to improve the quality of the standard company.